Pengaruh Promosi Media Sosial dan Word of Mouth Terhadap Loyalitas Pelanggan di Bengkel Collective Carbon Works - Nur Yasin, Thaufan Alif; Raskadi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to examine the effect of social media promotion and Word of Mouth on customer loyalty at Collective Carbon Works Workshop. The research employed a quantitative approach, with data collected through questionnaires distributed to 96 respondents. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that, partially, social media promotion has a positive and significant effect on customer loyalty. Similarly, Word of Mouth also has a positive and significant effect and demonstrates a stronger influence on customer loyalty. Simultaneously, social media promotion and Word of Mouth significantly affect customer loyalty. The coefficient of determination (R²) of 0.313 indicates that 31.3% of the variation in customer loyalty can be explained by the two independent variables, while the remaining 68.7% is influenced by other factors outside the research model. These findings highlight the importance of effective social media promotion strategies and positive interpersonal communication in enhancing customer loyalty in the automotive service industry.